The Study of Resource Allocation among Software Development Phases: An Economics-Based Approach. (12th January 2012) - Yiftachel, Peleg; Hadar, Irit; Peled, Dan; Farchi, Eitan; Goldwasser, Dan
Abstract : This paper presents an economics-based approach for studying the problem of resource allocation among software development phases. Our approach is structured along two parallel axes: theoretical and empirical. We developed a general economic model for analyzing the allocation problem as a constrained profit maximization problem. The model, based on a novel concept of software production function, considers the effects of different allocations of development resources on output measures of the resulting software product. An empirical environment for evaluating and refining the model is presented, and a first exploratory study for characterizing the model's components and developers' resource allocation decisions is described. The findings illustrate how the model can be applied and validate its underlying assumptions and usability. Future quantitative empirical studies can refine and substantiate various aspects of the proposed model and ultimately improve the productivity of software development processes.